Karakteristik Term At-Tijarah, Al-Bai’u, Tadayantum dan Isytara dalam Al-Qur’an - Masyhari Yanto; Ahmad Madani; Ghozi Mubarok (LP2M Universitas Ibrahimy, 2025)
This journal discusses the characteristics of trade terms in Islamic economics, such as At-Tijarah, Al-Bai'u, Tadayantum, and Isytara, based on the perspective of the Al-Qur'an. In this context, At-Tijarah is defined as economic activity that is not only focused on material gain, but also reflects moral and ethical values. The Al-Bai'u concept emphasizes the importance of honesty and transparency in transactions, while Tadayantum regulates lending and borrowing practices by avoiding usury and emphasizing justice. This journal also highlights Islamic economic principles that encourage ethical, fair and responsible business behavior. Through a qualitative approach and analysis of the text of the Koran, this research aims to provide a deeper understanding of the application of Islamic economic principles in everyday life, as well as their contribution to the welfare of wider society.